Analisis potensi penerimaan retribusi pelayanan pasar pada PD. Pasar di Kota Manado - Kumendong, Jannifer Vilisia; Morasa, Jenny; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2019)
Market service retribution is one Local Own-Source Revenue that used to financing regional expenditure. The aim of this study is to understand the income potential of the market service retribution in Manado City in period of 2017 to 2018. This study uses descriptive qualitative as method of analysis. The result shows that potential market retribution in period of 2017 to 2018 had increased. The greatest market potential service retribution in 2018 found in Bersehati Market, Pinasungkulan Market, and â€œShopping Centerâ€. The income potential has increase on Bersehati Market for about Rp 4,186,080,000 which caused by seller increasing as same as Pinasungkulan Market and Shopping Centers with income potential respectively about Rp 792,000,000 and Rp 612,720,000. The market with the smallest income potential is called â€œJalan Rodaâ€ with value of Rp. 149,040,000 with 69 selling sites. Overall, optimal income potential of 2018 for retribution of market service increase from Rp 6,100,920,000 to Rp. 6,551,280,000 accompany by seller increase.